Hubungan Kemampuan Bahasa Arab terhadap Prestasi Menghafal Al-Qur’an Santri Kelas XI SMA Cahaya Qur’an Cibungbulang Bogor Tahun Ajaran 2019/2020 - Abrar, Muh.; Asriani (Al-Ubudiyah: Jurnal Pendidikan dan Studi Islam, 2023)
This study aims to examine how strong the relationship between mastery of Arabic lessons on the ability to memorize Al-Qur'an and how significant is the relationship between mastery of Arabic learning and the ability to memorize Al-Qur'an in class XI students in Madrasah Aliyah Islamic boarding school tahfidz qur'an Ummul quro al-Islami bogor in the academic year 2019/2020. This research is a field research, while the approach to this research is a quantitative approach, meaning that the objectivity of the research design is carried out by using statistical processing figures, structures and controlled experiments. Judging by the population and sempel, this study is a population study, because it involves all research subjects, namely XI class. The data collection technique used questionnaire distribution documentation. The data obtained were analyzed  using quantitative  statistics.The Arabic language skills of  students of KLS XI  Madrasah  Aliyah Islamic Boarding School Tahfidzul Qur‘an Cahaya Qur’an Cibungbulang in the Academic Year 2019/2020. In very  good  category.  This  can  be  seen  from  the analysis  of  the  ability  to  memorize  students of  Kls  XI Madrasah Aliyah Islamic Boarding School Tahfidzul Qur‘an Cahaya Qur’an Cibungbulang in the Academic Year 2019/2020 in good categories In this case it can also be seen from the analysis. Based on the spread of the lift carried out by the researcher on the correlative quantitative analysis of the results of the study, it shows that there is an influence between the ability of the Arabic language to the ability to memorize the students of Islamic class XI Madrasah Aliyah Islamic Boarding School Tahfidzul Qur’an Cahaya Qur’an Cibungbulang in the Academic Year 2019/2020. The results of this study are expected to contribute to the knowledge of teachers, students, parents, boarding school and other researchers that the level of Arabic language proficiency can affect the memorization of the Qur'an.